Missing C, supplemental D and supplemental premolar all in one quadrant: a case report - E. EL-BAHANNASAWY & D. E. FUNG (Paediatric Dentistry, 2004)
This case report describes a non-syndromic Caucasian patient who presented with a missing upper right primary canine and a supplemental upper right primary first molar. Later, a supplemental premolar developed in the upper right quadrant.